Perilaku Hidup Bersih dan Sehat Guna Pencegahan Penyakit DBDPada Masyarakat Dusun Ngogak - Rahayu, Sang Ayu Putu; Septian Akbar Noor Wahyu Hardi; Hastari, Dinar Yana; Laila, Zamzammaimatul Zalfa (Jurnal Bina Desa, 2025)
Dengue fever is one of the endemic diseases that can be a major threat to civilization, especially in tropical areas such as Indonesia. Socialization of clean and healthy living behavior (PHBS) is very important in an effort to prevent and control the spread of this disease. The purpose of this study was to increase the awareness and knowledge of the Ngogak Hamlet community about the need to implement PHBS and dengue prevention methods. This socialization was held at the village hall and involved 41 people from Ngogak Hamlet. The purpose of this socialization is to provide education to the community so that they know how to implement clean and healthy daily living behaviors and also the prevention of dengue disease with the 3M PLUS method.